A characterization of adjunction in a many-valued modal system - Hércules de Araújo Feitosa; Romulo Albano de Freitas (CQD Revista Eletrônica Paulista de Matemática, 2025)
Galois connections are pairs of functions, defined over ordered sets, that preserve some particular aspects. They are studied in the context of algebraic structures. As a logic topic, we take the four-valued logic PM4N that contemplates, at least, two modal operators for the notions of necessary and possible. In this paper, we develop a particular four-valued implication for PM4N, which constitutes a Galois pair with the two modal operators. Then, we show some properties of the logic just considering the correlates algebraic developments.